Analisis Yuridis Terhadap Putusan Pengadilan yang Membebaskan Pengedar Narkotika Golongan I(sabu-sabu) (Studi Kasus Putusan Nomor 17/pid.sus/2022/pn. plk) - Dedo Ngara, Rambu Claudia Magi; Medan, Karolus Kopong; Leo, Rudepel Petrus (Artemis Law Journal, 2024)
The Palangkaraya District Court's decision to acquit narcotics defendants sparked demonstrations because it was deemed not to reflect justice. This research aims to analyze the basis of the judge's considerations in the court decision that acquits a Class I methamphetamine narcotics dealer who has fulfilled the principles of justice. The method used is normative juridical with a statutory approach and a conceptual approach, the data sources used are primary and secondary data sources and the data analysis technique used is qualitative analysis. Based on the research and analysis carried out by the author in the decision of the Narcotics Trafficking Crime Court Number 17/Pid.Sus/2022/PN.PLk Palakaraya, the defendant Salihin Saleh Abdullah was declared guilty based on the second alternative charge of Article 112 Paragraph 2 of Republic of Indonesia Law Number 35 of 2009 concerning Narcotics. The defendant was declared to have violated these provisions because without permission or against the law he possessed, stored, controlled or provided non-plant class I narcotics, weighing more than 5 grams. The basis of the judge's consideration in handing down the decision to acquit the Class I methamphetamine narcotics dealer Number 17/Pid.Sus/2022/PN.PLk was based on juridical considerations as the main approach. Still, the article applied was not relevant to Article 112 paragraph (2) of Republic of Indonesia Law No. . 35 of 2009 concerning Narcotics, namely that the defendant was guilty of trafficking class I narcotics exceeding 5 grams in weight. The value of justice in Palakaraya's decision on the narcotics trafficker, the trial process in this case went well, but the inaccurate application of the article could harm procedural justice. contained in the decision.